Examining the Relative Contribution of Social Support and Father Involvement to Psychological Well-Being in Early Adult Women - Nadya Ayundha Novem Ramaniya; Rizky Putra Santosa (Universitas Katolik Soegijapranata, 2026)
Young adult women are in a developmental phase that demands independence and entails various transitional pressures affecting their psychological well-being. This study aims to examine the influence of father involvement and social support on the psychological well-being of young adult women. The research hypothesis is that father involvement and social support significantly predict the psychological well-being of young adult women. A quantitative approach using linear regression was applied to 185 female participants aged 18–25 years, selected via purposive sampling, who were measured using the Inventory of Father Involvement (IFI), the Multidimensional Scale of Perceived Social Support (MSPSS), and Ryff’s Psychological Well-Being Scales (SPWB). The results indicate that father involvement (β=0.235; p0.001) and social support (β=0.347; p0.001) each significantly predict psychological well-being. Early-adult women with high father involvement and strong social support tend to have better psychological well-being, making the strengthening of these two factors crucial in efforts to support the mental health of early-adult women.